Evaluation of land use potential for quarrying area around Ramganjmandi (Kota, Rajasthan), India - Sharma D.K.; Saharan M.R.; Parihar S.K. (My University, 2025)
Large opencast mining leads to problems of land degradation and calls for quarry planning, particularly reclamation and post-quarried land use aspect of secondary utilisation mined out areas effectively. The problem becomes more complex as quarrying operations approach more densely populated areas and forest areas. The aim of the present study is to outline appropriate potential, secondary use for quarried land for which two approaches, first based on logical study of natural and cultural parameter, and second approach is computer-aided and uses a model to decide the priorities for the best suited quarried land uses. A case study of Satalkhedi Laxmipura area in Ramganjmandi, Kota (Rajasthan), India, has been presented.